Pengembangan E-Learning Menggunakan LMS Moodle pada Pendidikan Dasar Perkoperasian bagi Anggota Koperasi Mahasiswa UNY - Andri Yuwanto; Handaru Jati (Journal of Information Technology and Education (JITED), 2024)
The purposes of this research are for: (1) Create an e-learning website for Basic Cooperative Education KOPMA UNY. (2) Testing the quality level of the E-Learning website developed for KOPMA UNY Cooperative Basic Education according to media experts, material experts and users. The type of research used is Research and Development (R&D). While the development model in this research is the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). This research was conducted at KOPMA UNY with research subjects as media experts, material experts and new members of KOPMA UNY as E-Learning users. Data collection techniques used were interviews and questionnaires. The results of this research are (1) E-Learning Websites that are able to operate properly so that it makes it easier for users to access learning anywhere at any time (2) The level of quality of the e-learning website according to media experts is "very high quality", according to material experts "very high quality" and from the opinion of users it gets an assessment of "very high quality".